A mechanism converting psychosocial stress into mononuclear cell activation - Bierhaus, Angelika; Wolf, Jutta; Andrassy, Martin; Rohleder, Nicolas; Humpert, Per Magnus; Petrov, Dimitri; Ferstl, Roman; Eynatten, Maximilian von; Wendt, Thoralf Manfred; Rudofsky, Gottfried; Joswig, Martina; Morcos, Michael; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
Little is known about the mechanisms converting psychosocial stress into cellular dysfunction. Various genes, up-regulated in atherosclerosis but also by psychosocial stress, are controlled by the transcription factor nuclear factor κB (NF-κB). Therefore, NF-κB is a good candidate to convert psychosocial stress into cellular activation. Volunteers were subjected to a brief laboratory stress test and NF-κB activity was determined in peripheral blood mononuclear cells (PBMC), as a window into the body and because PBMC play a role in diseases such as atherosclerosis. In 17 of 19 volunteers, NF-κB was rapidly induced during stress exposure, in parallel with elevated levels of catecholamines and cortisol, and returned to basal levels within 60 min. To model this response, mice transgenic for a strictly NF-κB-controlled β-globin transgene were stressed by immobilization. Immobilization resulted in increased β-globin expression, which could be reduced in the presence of the α1-adrenergic inhibitor prazosin. To define the role of adrenergic stimulation in the up-regulation of NF-κB, THP-1 cells were induced with physiological amounts of catecholamines for 10 min. Only noradrenaline resulted in a dose- and time-dependent induction of NF-κB and NF-κB-dependent gene expression, which depended on pertussis-toxin-sensitive G protein-mediated phosphophatidylinositol 3-kinase, Ras/Raf, and mitogen-activated protein kinase activation. Induction was reduced by α1- and β-adrenergic inhibitors. Thus, noradrenaline-dependent adrenergic stimulation results in activation of NF-κB in vitro and in vivo. Activation of NF-κB represents a downstream effector for the neuroendocrine response to stressful psychosocial events and links changes in the activity of the neuroendocrine axis to the cellular response.
Gesehen am 29.03.2021